Higher volume providers are associated with improved outcomes following ERCP for the palliation of malignant biliary obstruction. (January 2020) - Harvey, Philip R; Baldwin, Simon; Mytton, Jemma; Dosanjh, Amandip; Evison, Felicity; Patel, Prashant; Trudgill, Nigel J
Abstract: Background: Relieving malignant biliary obstruction improves quality of life and permits chemotherapy. Outcomes of endoscopic retrograde cholangio-pancratography(ERCP) in inoperable malignant biliary obstruction have been examined in a national cohort to establish factors associated with poor outcomes. Methods: Hospital Episode Statistics include diagnostic and procedural data for all NHS hospital attendances in England. Patients from 2006 to 2017 with a Hepaticopancreaticobiliary (HPB) malignancy who had undergone ERCP were studied. Patients undergoing a potentially curative operation were excluded. Associations between demographics, co-morbidities, unit ERCP volume and mortality were examined by logistic regression. Findings: 39, 702 patients were included; 49.4% were male; median age was 75 (IQR 66–88)years. Pancreatic cancer was the most common tumour (63.9%). Mortality was 4.1%, 9.7% and 19.1% for 7-day, in hospital and 30-day respectively. On multivariable analysis: men (OR 1.20(95%CI 1.14–1.26), p < 0.001); increasing age quintile 78–83(1.73(1.59–1.89), p < 0.001), >83(2.70(2.48–2.94), p < 0.001); most deprived quintile (1.21(1.11–1.32), p < 0.001); increasing co-morbidity score >20(3.36(2.94–3.84), p < 0.001); small bowel malignancy (1.45(1.22–1.72), p < 0.001), intrahepatic biliary malignancy(1.10(1.03–1.17), p  = 0.005) and year of ERCP 2006/07 (1.37(1.22–1.55), p < 0.001) were associated with increased 30-day mortality. Extrahepatic biliary tree cancers (0.67(0.61–0.73), p <0.001), high volume providers of ERCP (>318 annually, 0.91(0.84–0.98), p  = 0.01) and high volume of ERCP for malignant obstruction (>40 annually (0.91(0.85–0.98), p  = 0.014) were negatively associated with 30-day mortality. Patients were less likely to require a second ERCP in high volume providers (>318, 8.0%) compared to low volume ((<204, 13.4%), p <0.001). Interpretation: Short term mortality in patients with malignant biliary obstruction following ERCP was high. 30-day mortality was positively associated with increasing age and co-morbidity, men, deprivation, and earlier year of ERCP and negatively with extrahepatic biliary tree cancer and high volume ERCP providers. Funding: Internal funding only